(untitled) - Smith, Kelvin (London, 2004)
This book takes its title very seriously. It is a practical guide to the implementation of the Freedom of Information Act 2000. Its combination of descriptions, checklists, models and practical examples will enable all those involved in the discharge of this important enactment to do so without fear or worry. Written by an expert at the National Archives, it avoids describing Freedom of Information in legal terms and instead focuses on implementation of the Act from a user's point of view; pointing the reader to those parts of it which will affect implementation procedures. Time is running out in the countdown to full implementation of the Act by January 2005 so this guide provides all the information need to ensure efficient and speedy compliance with the Act. It covers both preparing for implementation (staffing infrastructure, action planning, records management and training) and actual implementation (use of ICT, logging systems and handling requests). The book also includes an examination of how FOI links with other legislation such as data protection and human rights. Full of checklists and toolkits, the book also comes with free, downloadable training materials. This is essential reading for all in public services work, particularly those involved in customer enquiries, record keeping and policy making.
Keywords: Information policy,Information resources management